Hotel Trópico : Brazil and the challenge of African decolonization, 1950-1980 - Dávila, Jerry, 1970- (e-Duke books scholarly collection., 2010)
A study of perceptions of race and national identity in Brazil's conflicted effort to build relations with African nations in the second half of the twentieth century.